Versatile Cu-II metal-organic framework exhibiting high gas storage capacity with selectivity for CO2: conversion of CO2 to cyclic carbonate and other catalytic abilities - De, Dinesh; Pal, Tapan K.; Neogi, Subhadip; Senthilkumar, S.; Das, Debasree; Sen Gupta, Sayam; Bharadwaj, Parimal K. (Chemistry-A European Journal, 2016)
A linear tetracarboxylic acid ligand, H4L, with a pendent amine moiety solvothermally forms two isostructural metal-organic frameworks (MOFs) L-M (M=Zn-II, Cu-II). Framework L-Cu can also be obtained from L-Zn by post- synthetic metathesis without losing crystallinity. Compared with L-Zn, the L-Cu framework exhibits high thermal stability and allows removal of guest solvent and metal-bound water molecules to afford the highly porous, L-Cu. At 77K, L-Cu absorbs 2.57wt% of H-2 at 1bar, which increases significantly to 4.67wt% at 36bar. The framework absorbs substantially high amounts of methane (238.38cm(3)g(-1), 17.03wt%) at 303K and 60bar. The CH4 absorption at 303K gives a total volumetric capacity of 166cm(3)(STP)cm(-3) at 35bar (223.25cm(3)g(-1), 15.95wt%). Interestingly, the NH2 groups in the linker, which decorate the channel surface, allow a remarkable 39.0wt% of CO2 to be absorbed at 1bar and 273K, which comes within the dominion of the most famous MOFs for CO2 absorption. Also, L-Cu shows pronounced selectivity for CO2 absorption over CH4, N-2, and H-2 at 273K. The absorbed CO2 can be converted to value-added cyclic carbonates under relatively mild reaction conditions (20bar, 120 degrees C). Finally, L-Cu is found to be an excellent heterogeneous catalyst in regioselective 1,3-dipolar cycloaddition reactions (click reactions) and provides an efficient, economic route for the one-pot synthesis of structurally divergent propargylamines through three-component coupling of alkynes, amines, and aldehydes.
Keywords: click reactions; CO2 absorption; cyclic carbonate; heterogeneous catalysis; metal-organic frameworks

Devising chemically robust and cationic Ni(II)-MOF with nitrogen-rich micropores for moisture-tolerant CO2 capture: highly regenerative and ultrafast colorimetric sensor for TNP and multiple Oxo-anions in water with theoretical revelation - Goswami, Ranadip; Seal, Nilanjan; Dash, Soumya Ranjan; Tyagi, Anshu; Neogi, Subhadip (ACS Applied Materials & Interfaces, 2019)
Metal-organic frameworks (MOFs) show distinctive superiority for carbon dioxide (CO2) capture and luminescent sensing of toxic pollutants over other materials where combination of both of these properties together with improvement of hydrolytic stability and pore functionality is critical to environmental remediation applications. The Ni(II) framework [Ni-2(mu 2OH)(azdc)(tpim)](NO3)center dot 6DMA center dot 6MeOH (CSMCRI-3) (tpim = 44'4(2)-(1H-imidazole-245-triyl)tripyridine H(2)azdc = azobenzene-44'-dicarboxylic acid DMA = dimethylacetamide CSMCRI = Central Salt & Marine Chemicals Research Institute) encompassing cationic [Ni-2(mu(2)-OH)(CO2)(2)] SBUs is solvothermally synthesized from nitrogen-rich and highly fluorescent organic struts. The noninterpenetrated structure containing free nitrogen atom affixed microporous channels is stable in diverse organic solvents and weakly basic and acidic aqueous solutions. The activated MOF (3a) exhibits strong CO2-framework interaction and extremely selective CO2 adsorption over N-2 (292.5) and CH4 (11.7). Importantly water vapor exposure does not affect the surface area and/or multiple CO2 uptake-release cycles signifying potential of the porous structure for long-term use under humid conditions. Aqueous-phase sensing studies illustrate extremely specific and ultrafast detection of explosive 246-trinitrophenol (TNP) via remarkable fluorescence quenching (K-SV = 1.3 x 10 (5) M-1) with a 0.25 ppm limit of detection (LOD). Furthermore 3a serves as unique luminescent probe for highly discriminative and quick responsive detection of three noxious oxo-anions (Cr2O7 (2-) CrO4 (2-) MnO4-) in water via noteworthy turn-off responses and extreme low LODs (Cr2O7 (2-) 0.9; CrO4 (2-) 0.29; MnO4- 0.25 ppm). It is imperative to stress the outstanding reusability of the MOF toward multicyclic sensing of all four major water contaminants alongside visible colorimetric changes upon individual analyte detection. Mechanistic insights in light of the electron transfer route together with density functional theory calculations portray the influence of pore functionalization in framework-analyte interactions including alternation in energy levels where varying degrees of contribution of energy transfer explicitly authenticates high quenching of the material.
Keywords: chemically robust cationic MOF; DFT calculation; fast responsive detection; humid CO2 capture; TNP and oxo-anion sensing

Dual-catalyst engineered porous organic framework for visible-light triggered, metal-free and aerobic sp(3) C-H activation in highly synergistic and recyclable fashion - Kumar, Gaurav; Dash, Soumya Ranjan; Neogi, Subhadip (Journal of Catalysis, 2021)
Photoredox and organo-catalysis denote powerful construction tools for new classes of carbon-carbon bonds, where incisive amalgamation of both the approaches over a single, recyclable platform can bring about synergic and eco-friendly reactions under mild conditions. Aiming at enamine-based photoredox catalysis for atom-economic and metal-free sp(3 )C-H activation, an amide-based two-dimensional (2D) porous organic framework (POF) is devised. The pendent -NH2 groups are judiciously anchored with two catalytic stations viz. Rose Bengal and L-proline, through stepwise variation of solid phase peptide synthesis. The dual-catalyst engineered POF represents a fully organic material that synergistically performs visible-light triggered oxidative Mannich reaction to produce biorelevant heterocycle beta-amino ketone in excellent yield at room temperature, using oxygen as clean and selective oxidant. Importantly, activity of this bi-functionalized catalyst compares favorably well to individual homogeneous counterparts. The covalently modified framework demonstrates economic viability via gram-scale synthesis besides admirable reusability, and proves to be effective for nineteen varieties of substrates. The photocatalytic path is detailed from efficient energy transfer from host polymer to substrate in light of experimental and theoretical studies, which provides proof-of-concept to the photo-organo combined mechanism. The material benefits heterogenising two homogeneous catalysts, besides excluding additional steps of conventional Mannich reactions, and offers a step-forward to smart and green cross-dehydrogenative coupling reactions. (C) 2020 Elsevier Inc. All rights reserved.
Keywords: Atom-economy; C-H activation; Dual-catalyst engineering; Metal-free reaction; Photo-organo catalysis; Porous organic framework